Sildenafil Is Associated With Reduced Device Thrombosis and Ischemic Stroke Despite Low-Level Hemolysis on Heart Mate II Support. (November 2017) - Saeed, Omar; Rangasamy, Sabarivinoth; Selevany, Ibrahim; Madan, Shivank; Fertel, Jeremy; Eisenberg, Ruth; Aljoudi, Mohammad; Patel, Snehal R.; Shin, Julia; Sims, Daniel B.; Reyes Gil, Morayma; Goldstein, Daniel J.; et al.
Abstract : Background: Persistent low-level hemolysis (LLH) during continuous-flow mechanical circulatory support is associated with subsequent thrombosis. Free hemoglobin from ongoing hemolysis scavenges nitric oxide (NO) to create an NO deficiency which can augment platelet function leading to a prothrombotic state. The phosphodiesterase-5 inhibitor, sildenafil, potentiates NO signaling to inhibit platelet function. Accordingly, we investigated the association of sildenafil administration and thrombotic events in patients with LLH during Heart Mate II support. Methods and Results: A single-center review of all patients implanted with a Heart Mate II who survived to discharge (n=144). LLH was defined by a discharge lactate dehydrogenase level of 400 to 700 U/L. Patients were categorized as (1) LLH not on sildenafil, (2) LLH on sildenafil, (3) no LLH not on sildenafil, and (4) no LLH on sildenafil. Age, sex, platelet count, and mean platelet volume were similar between groups. Seventeen patients had either device thrombosis or ischemic stroke. Presence of LLH was associated with a greater risk of thrombosis (adjusted hazard ratio, 15; 95% confidence interval, 4.5–50; P <0.001 versus no LLH, not on sildenafil). This risk was reduced in patients with LLH on sildenafil (adjusted hazard ratio, 1.7; 95% confidence interval, 0.2–16.1; P =0.61). Device thrombosis and ischemic stroke were associated with an increase in mean platelet volume (9.6±0.5 to 10.9±0.8 fL, P <0.001). Patients with LLH not on sildenafil had a greater increase in mean platelet volume in comparison to those with LLH on sildenafil ( P <0.001). Conclusions: Sildenafil is associated with reduced device thrombosis and ischemic stroke during ongoing LLH on Heart Mate II support. Abstract : Supplemental Digital Content is available in the text.